Great Carrier Reef - Stremer, Jessica (Books for a better earth., 2023)
"Off the coast of Florida, 200 feet beneath the waves, a massive aircraft carrier lies on the bottom of the ocean floor. Once an unsinkable ship, the Mighty O is now an underwater city teeming with marine life. After 25 years of service in the Navy, the ship took on a new mission as an artificial reef."-